2009
DOI: 10.1159/000229997
|View full text |Cite
|
Sign up to set email alerts
|

Korea Red Ginseng on Helicobacter pylori-Induced Halitosis: Newer Therapeutic Strategy and a Plausible Mechanism

Abstract: Background: Gas chromatographic documentation of volatile sulfur compounds in Helicobacter pylori cultures and the amelioration of halitosis after eradication suggested a causal link between H. pylori infection and halitosis. Aim: We hypothesized that Korea red ginseng can relieve H. pylori-associated halitosis based on their anti-inflammatory and cytoprotective actions in H. pylori-associated gastritis. Methods: Eighty-eight functional dyspepsia patients presenting with either subjective halitosis or objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…To increase eradication rates of first-line therapy, several clinical trials involving extending treatment duration to more than one week, use of higher doses of per protocol (PP), and/or new antibiotics such as quinolones, use of quadruple therapy, or addition of probiotics, vitamin C, bovine lactoferrin, ginseng, wine, garlic, honey, and cranberry have been carried out [11][12][13][14][15]. Previous studies have suggested that Korean red ginseng 1) inhibits H. pylori colonization, 2) exhibits antioxidative and antiinflammatory effects during H. pylori infection, 3) provides efficient restorative action, 4) inhibits expression of genes associated with generation of volatile sulfur compounds (VSCs), and 5) increases eradication rates in addition to attenuating H. pyloriassociated halitosis [16][17][18][19]. Here, we investigated the effects of supplementation of triple therapy with Korean red ginseng on both H. pylori eradication rates and H. pylori-associated halitosis.…”
Section: Efficacy Of Korean Red Ginseng Supplementation On Eradicatiomentioning
confidence: 99%
“…To increase eradication rates of first-line therapy, several clinical trials involving extending treatment duration to more than one week, use of higher doses of per protocol (PP), and/or new antibiotics such as quinolones, use of quadruple therapy, or addition of probiotics, vitamin C, bovine lactoferrin, ginseng, wine, garlic, honey, and cranberry have been carried out [11][12][13][14][15]. Previous studies have suggested that Korean red ginseng 1) inhibits H. pylori colonization, 2) exhibits antioxidative and antiinflammatory effects during H. pylori infection, 3) provides efficient restorative action, 4) inhibits expression of genes associated with generation of volatile sulfur compounds (VSCs), and 5) increases eradication rates in addition to attenuating H. pyloriassociated halitosis [16][17][18][19]. Here, we investigated the effects of supplementation of triple therapy with Korean red ginseng on both H. pylori eradication rates and H. pylori-associated halitosis.…”
Section: Efficacy Of Korean Red Ginseng Supplementation On Eradicatiomentioning
confidence: 99%
“…The fact that no significant difference observed in VSC levels according to severity of esophageal mucosal injury defined by LA classification and minimal lesion showed highest VSC concentration leaves possible insights of H2S role in pathogenesis of ERD like intervening of esophageal inflammation before the development of erosive lesions, sloughing of esophageal mucosa, and increased synthesis of VSCs in injured esophageal mucosa. [22][23][24] Currently, minimal change lesion is classified as NERD because of no definite presence of erosive or ulcerative changes in esophagogastric junction, [14][15][16] but there is high possibility that minimal change lesion could be one of early ERD supported with our objective finding that minimal change lesion showed highest levels of VSCs than either NERD or ERD. Hiatal hernia is closely associated with GERD and ERD was seen more frequently in patients with hiatal hernia than in patients without hiatal hernia.…”
Section: Discussionmentioning
confidence: 62%
“…Five milliliters Minimal change lesion; classified as part of NERD based on reference. [14][15][16] gastric juices were aspirated from gastric corpus during the endoscope procedure using aspiration tube inserted onto biopsy channel (Olympus, Tokyo, Japan) and were stored at −70 o C deep freezer until the assay. After several times of trials and errors at different temperature for the evaporating of gastric juices, we could success in final decision that 60 o C were quite ideal for evaporating gastric juices for gas chromatography.…”
Section: Gas Chromatography For Gastric Juice Vsc Concentrationsmentioning
confidence: 99%
“…We found that Korean red ginseng can resolve halitosis through either regulation of the genes responsible for VSC synthesis or direct inhibition of H. pylori infection. The evidence is as follows: H. pylori increased the levels of cystathionine g-lyase (CSE) and cystathionine b-synthase (CBS) mRNA, which encode inflammatory cytokines that promote VSC synthesis, and of the inflammatory mediators IL-1b, IL-8, and IL-6; Korean red ginseng significantly attenuated CSE and CBS mRNA production concomitant with decreased expression of the respective proteins; significant reductions in halimeter ppb levels (<50) were obtained after H. pylori eradication and red ginseng supplementation [47]. Thus, halitosis appears to be mechanistically associated with H. pylori infection, and Korean red ginseng supplementation following a successful eradication regimen could alleviate troublesome halitosis.…”
Section: Korean Red Ginseng In the Treatment Of Halitosis: Evidences mentioning
confidence: 99%
“…Four patients were lost to follow-up in the Korean red ginseng group and one patient in the eradication alone group [68]. In a previous published trial, we assessed the eradication rate under the same protocol (i.e., eradication alone vs. eradication plus 10 weeks of Korean red ginseng supplementation), although over a different time course [47,49]. By combining the data from the current and the previous trial to determine the overall efficacy of Korean red ginseng supplementation on the H. pylori eradication rate, we found that a 10-week course of Korean red ginseng (Jeongkwanjang red ginseng capsule, 2.7 g/day; Korea Ginseng Cooperation, Daejeon, Korea) supplementation significantly augmented eradication rates (eradication alone group 75 of 102, 73.5% vs. eradication plus Korean red ginseng group 82 of 90, 91.1%; p<0.005).…”
Section: Quantitative Advantage Of Korean Red Ginseng In H Pylori Inmentioning
confidence: 99%